Characteristics and prognostic factors of metachronous second primary upper gastrointestinal cancer - Jung, Jin-On; Schulz, Erik R.; Nienhüser, Henrik; Peters, Leila; Müller, Beat P.; Diener, Markus K.; Büchler, Markus W.; Schmidt, Thomas (Journal of surgical research, 2021)
BACKGROUND: Patients with metachronous malignancies before carcinomas of the upper gastrointestinal tract were analyzed regarding clinical parameters, oncological outcome, and prognosis. - METHODS: We analyzed the data of 1583 patients with gastroesophageal cancer who underwent oncological resections between 2002 and 2018. Of 1583 patients, 172 had a malignant tumor before the upper gastrointestinal cancer (second primary carcinomas) and 1411 without preceding malignancies served as the control group. The analyses were performed between both groups and within the subgroup of second primary carcinomas. - RESULTS: Patients with second primary carcinomas were older (P < 0.0001), had more comorbidities (P < 0.0001), and underwent longer surgical resections (P = 0.0024). They had lower (y)pT-categories (P = 0.0427) and had longer stays in intensive care unit (P = 0.0002) and hospital (P = 0.0018). R0-resection was more frequent (P = 0.0275) while having more surgical complications (P = 0.0378). The median survival was 39.5 mo (primary carcinoma) versus 32.9 mo for (second primary carcinoma) and was not significantly different (P = 0.5359).In the subgroup analysis of second primaries, there were no significant survival differences depending on primary tumor entity (P = 0.4989). pT status (P = 0.0062), pN status (P < 0.0001), pM status (P < 0.0001), and R-status (P < 0.0001) were significant prognostic factors. A time period >9 y after the primary cancer could be identified as a novel and beneficial survival factor (P = 0.0496). Most patients with primary colorectal, prostate, hematogenous, or breast cancer had adenocarcinoma, whereas patients with initial otolaryngologic cancers mainly had squamous cell carcinoma. - CONCLUSIONS: Second primary carcinomas of the upper gastrointestinal tract show distinct clinical and oncological characteristics. Common prognostic factors are applicable, and oncologic resection is recommended.